Behavioral and Neurochemical Consequences of Subacute Acetamiprid Administration in a Mice Model - Sherif, Sinan M.; Alzubaidy, Muna Hazim (Journal of applied veterinary sciences, 2025)
Acetamiprid, a neonicotinoid insecticide, effectively controls a wide range of crop pests and fleas on livestock and pets. This research examined the neurobehavioral and biochemical consequences of subacute, low-dose oral exposure to acetamiprid in adult mice. The study population was divided into four groups (5 mice/group), including one control group, while the remaining groups received 3.14, 6.29, and 12.59 mg/kg acetamiprid orally three times per week for a duration of 28 days. Behavioral evaluations indicated a clear dose-dependent decline in motor performance, spatial learning, and memory. Reduced rearing activity in the open-field test, poorer outcomes in the negative geotaxis assessment, and fewer head-poking events were indicative of these impairments. Animals treated with higher doses (6.29 and 12.59 mg/kg) also exhibited shorter wire-hanging endurance times and reduced alternation in the T-maze, pointing to deficits in working memory. Biochemical investigations revealed notable reductions in cholinesterase activity in both plasma and brain tissues, coupled with pronounced oxidative stress, as evidenced by increased malondialdehyde levels and decreased glutathione content. Such alterations emerged as early as the 14th day of treatment and persisted until the 28th day. Collectively, the results indicate that subacute acetamiprid exposure can interfere with cholinergic signaling, promote oxidative injury, and compromise both cognitive and motor abilities in mice. Additional studies are needed to clarify the long-term neurodevelopmental risks associated with neonicotinoid exposure in mammals.